DEVELOPMENT OF DIGITAL CONTENT ASSISTED LANGUAGE LEARNING (DCALL) MODEL TO IMPROVE WRITING SKILLS - Jusrin Efendi Pohan; Esra Perangin-Angin (Universitas Labuhanbatu, 2026)
Purpose – this study differs from previous research in that it focuses on developing the DCALL model in writing learning. The main target is students' writing skills in any text, supported by an application integrated with writing learning materials.Methodology – This research was conducted by developing a research product using the Plomp development model, which consists of preliminary research, prototype design, and evaluation. Each stage of this model is filled with activities that clearly describe the research process. The sampling technique used was purposive sampling, adjusted to the needs during the product trial, which consisted of high schools in Medan City, North Sumatra. The research instruments used consisted of questionnaires, observation sheets, and tests.Findings – The results of this study indicate that the Digital Content Assisted Language Learning (DCALL) model was categorized as valid, practical, and effective in teaching writing. Students find it easier and more practical to write any text after learning it with the aid of the technology used. The effectiveness of the DCALL model after being tested in the experimental class obtained a percentage of objectivity of 86.3%, audience 85.15%, and logic 83.9%. This indicates that the DCALL model can be applied according to the needs and characteristics of students and teachers. From a learning perspective, students are more interested in learning through applications in writing. Students are better able to formulate ideas and concepts within a systematic writing framework.Contribution – The development of the DCALL model is expected to facilitate student writing instruction. This learning model encourages students to be more active and creative in their writing. The implications of the DCALL model, after being tested in an experimental class, were that it was more dominant in expressing students' ideas and thoughts in writing. The design of the DCALL model guides students through writing steps that align with the characteristics of the text to be written.